Ti/Ni co-doped perovskite cathode with excellent catalytic activity and CO2 chemisorption ability via nanocatalysts exsolution for solid oxide electrolysis cell - Zhen, Shuying; Zhang, Lihong; Xu, Chunming; Zhang, Ding; Yi, Qun; Sun, Wang; Sun, Kening (Frontiers in Chemistry, 2022)
Carbon dioxide (CO2) gas is the main cause of global warming and has a significant effect on both climate change and human health. In this study, Ni/Ti co-doped Sr1.95Fe1.2Ni0.1Ti0.2Mo0.5O6-δ (SFNTM) double perovskite oxides were prepared and used as solid oxide electrolysis cell (SOEC) cathode materials for effective CO2 reduction. Ti-doping enhances the structural stability of the cathode material and increases the oxygen vacancy concentration. After treatment in 10% H2/Ar at 800 °C, Ni nanoparticles were exsolved in situ on the SFNTM surface (Ni@SFNTM), thereby improving its chemisorption and activation capacity for CO2. Modified by the Ti-doping and the in situ exsolved Ni nanoparticles, the single cell with Ni@SFNMT cathode exhibits improved catalytic activity for CO2 reduction, exhibiting a current density of 2.54 A cm2 at 1.8 V and 800 °C. Furthermore, the single cell shows excellent stability after 100 h at 1.4 V, indicating that Ni/Ti co-doping is an effective strategy for designing novel cathode material with high electrochemical performance for SOEC.